Effects of Peripartum Supplementation of β-Carotene on Postpartum Fertility in Lactating Kankrej Cows - Desai, Raj V; Nakhashi, Haresh C; Patil, Shrikant S; khatri, shweta P; Saini, Sachin; Suthar, Babulal N (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A study was undertaken to assess the effect of β-carotene supplementation on fertility in lactating Kankrej cows. Advanced pregnant cows (n=18) were randomly assigned into three groups. Experimental animals in Group I were fed on basal diet, while in Group-II and III were supplemented with 500 and 1000 mg of β-carotene/animal/day, respectively, for a period of 42 days, 21 days each before and after calving. All the cows were subjected to per-rectal and ultrasonographic observations at the 7th, 15th, 21st and 30th day postpartum. The gross uterine involution occurred at 28.50±1.50, 25.50±2.01 and 24±1.89 days in Group I, II and III, respectively. The diameter of the cervix was found to differ non-significantly between the groups on the 7th, 15th and 30th day in Group III from Group I and II. There was a highly significant reduction in the mean diameter of the gravid and non-gravid horn on the 7th day in Group II and III as compared to Group I, and also on the 21st and 15th day, respectively, within Group I and II. First service conception rate and overall conception rate were observed to be higher in Group III followed by Group II and I. It was concluded that β-carotene supplementation peripartum @ 1000 mg/animal/day for a period of 42 days accelerates uterine involution and improves postpartum fertility in dairy animals.